Epicardial pulsed-field ablation-impact of electric field and heat distribution induced by coronary metallic stents - Wang, Zhen; Liang, Ming; Sun, Jingyang; Zhang, Jie; Li, Yunhao; Xu, Lisheng; Han, Yaling (Frontiers in Cardiovascular Medicine, 2024)
Background: Pulsed-field ablation (PFA) technique as a nonthermal ablation technique.No study has yet evaluated the effect of the positional relationship between the ablation electrode (AE) and the coronary metal stent (CMS) on the electric field distribution and temperature distribution in epicardial ablation. Our study aimed to evaluate the effect of the CMS on the electric field as well as the temperature distribution in different models. Methods: Multi-angle modeling of the CMS and AE was performed. The PFA ablation region was evaluated with a field strength contour of 1000 V/cm, which was used to assess the validity of the two-dimensional (2D) model simulation data as well as the distribution of the multi-angle electric field and temperature in the three-dimensional (3D) model. Results: The presence of the CMS had little effect on the width of the ablation area (0.2 mm). In the 3D model, the temperature of the ablation area was highest when the angle between the AE and the CMS was in the 90°position (43.4°C, 41.3°C); a change in the distance between the AE and the CMS affected the temperature of the ablation area (maximum 2.1°C) and the width of the ablation (maximum 0.32 mm). Conclusion: The presence of the CMS distorts the distribution of the electric field, but does not produce a change in the extent of the ablation damage, nor does it bring thermal damage to the ablation region. Different simulation models give similar results in PFA calculations, and this study effectively reduces the complexity of modeling simulation.